Cornu cutaneum at an unusual site - Francis Leo Tauro; John Joseph S Martis; K Sijo John; K kumar Prem (Indian Journal of Plastic Surgery)
Cutaneous horn (cornu cutaneum) is a clinical diagnosis referring to a conical projection above the surface of the skin that resembles a miniature horn. The base of the horn may be flat, nodular or crateriform. The horn is composed of compacted keratin. Various histologic lesions have been documented at the base of the keratin mound and histological confirmation is often necessary to rule out malignant changes. Tenderness at the base of the lesion and lesions of larger size favour malignancy. Malignancy is present in 16-20% of the cases with squamous cell carcinoma being the most common type. We report a young male patient with a keratin horn on the right index finger tip.